Motivation-regulation Strategies for English Academic Reading among Undergraduate Students at a Private University - Nadeak, Ave Lucia; Kuswandono, Paulus (Universitas Pendidikan Ganesha, 2024)
Engagement with academic texts is essential in undergraduate education, contributing significantly to students’ intellectual development and academic achievement. This study aims to analyze the strategies used by undergraduate students at a university to regulate their motivation in reading academic texts. This study specifically examines the use of motivation regulation strategies, including intrinsic and extrinsic goals, help-seeking behavior, peer collaboration, and self-regulation. A mixed-methods research design was used, combining quantitative and qualitative data collected through closed-ended and open-ended questionnaires from students of the English Education Study Program. The results showed a dominant reliance on extrinsic motivators, such as achieving high grades, while intrinsic motivation was relatively weaker. Students tended to seek help from peers more often than lecturers, and self-regulation techniques such as skimming and selective reading were commonly used. This study encourages the development of targeted interventions to enhance intrinsic motivation and improve support mechanisms for students who face difficulties in academic reading. It is recommended that educators encourage the use of a balance of intrinsic and extrinsic motivation strategies to facilitate deeper engagement with academic materials.